Early onset sporadic colorectal cancer: Worrisome trends and oncogenic features. Issue 6 (June 2018) - Cavestro, Giulia Martina; Mannucci, Alessandro; Zuppardo, Raffaella Alessia; Di Leo, Milena; Stoffel, Elena; Tonon, Giovanni
Abstract: Early onset colorectal cancers, defined as arising before 50 years of age, are a growing health hazard in western and eastern countries alike. The incidence of colon and rectal cancers in young individuals is projected to increase by as much as 90% and 140%, respectively, by 2030. Although several known cancer risk factors (e.g. smoking, alcohol, dietary habits) have been investigated, there is no single compelling explanation for this epidemiological trend. While some early onset colorectal cancers have been associated with germline mutations in cancer predisposition genes, genetic syndromes are implicated in only a fraction of these cancers (20%) and do not explain the rising incidence. Colorectal neoplasms develop through microsatellite instability or chromosomal instability pathways, with most of the early onset colorectal cancers exhibiting microsatellite stable phenotypes. Genome-wide hypomethylation is a feature of a subgroup of early onset cancers, which appears to be correlated with chromosomal instability and poor prognosis.